Tribological behavior of diamond-like carbon thin films deposited by the pulse laser technique at different substrate temperatures. (November 2016) - Salah, Numan; Alshahrie, Ahmed; Iqbal, Javed; Hasan, P.M.Z.; Abdel-wahab, M.Sh.
Abstract: Diamond-like carbon (DLC) thin films were deposited by the pulse laser deposition at different substrate temperatures. They were deposited at the temperature range 100–500 °C and evaluated for their tribological behavior. The as-synthesized DLC films were characterized by different techniques. Ultrafine nanoparticles were observed in the deposited DLC films. The morphology of the deposited DLC films was significantly modified by increasing the substrate temperature. The particle size was increased from around 10 nm to approximately 30 nm by increasing the substrate temperature from 100 to 500 °C. The surface roughness was also increased, beside a formation of DLC clusters mainly at 500 °C. Raman and XPS spectra showed a significant improvement in the graphitization along with pronounced defects in the amorphous carbon structures in these DLC films. These modifications, induced by increasing the DLC substrate temperature have increased values of the friction coefficient and specific wear rate. These results showed that the DLC films with ultrafine nanoparticles have good prospect to be used as protective layers for metallic surfaces as they show low friction property and high wear ability. Graphical abstract: Highlights: DLC thin films were deposited by the PLD at different substrate temperatures (ST). They were evaluated for their tribological behavior as a function of ST. The morphology of the DLC films was significantly modified by increasing the ST. These modifications have increased the friction coefficient and specific wear rate. The DLC film with ultrafine nanoparticles showed excellent tribological properties.